Some industrial chemicals and dyestuffs (International Agency for Research on Cancer, 1982)
Evaluates the carcinogenic risk to humans posed by exposure to some Industrial Chemicals and Dyestuffs.
IARC monographs on the evaluation of carcinogenic risk of chemicals to humans ; Vol. 29
Keywords: Benzidines; benzen; benzidiny; karcinogeny; Benzene; Carcinogens; chemie, klinická chemie; onkologie